2005
DOI: 10.1002/chin.200547055
|View full text |Cite
|
Sign up to set email alerts
|

Mild and Chemoselective Deacetylation Method Using a Catalytic Amount of Acetyl Chloride in Methanol.

Abstract: Deprotection O 0345 Mild and Chemoselective Deacetylation Method Using a Catalytic Amount of Acetyl Chloride in Methanol. -The procedure allows the efficient removal of acetyl groups in the presence of other acid-sensitive protecting groups. -(YEOM, C.-E.; LEE, S. Y.; KIM, Y. J.; KIM*, B. M.; Synlett 2005, 10, 1527-1530; Sch. Chem., Seoul Natl. Univ., Seoul 151-747, S. Korea; Eng.) -Mais 47-055

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Purified sapogenin is an amorphous powder with a purity of 91.62% by HP 1100 HPLC (Agilent, Santa Clara, CA, U.S.A.) in the following operating conditions: column, Hypersil ODS (250 × 4.6 mm, 5 μm); flow phase, methanol/water (80:20); injection volume, 10 μL; flow rate, 1 mL/min; temperature, 25 °C; and wavelength, 218 nm. IR spectra and 1 H and 13 C NMR data showed that it had a sapogenin structure with formula C 30 H 48 O 5 , which is consistent with our former literature. 9 A total of 19 derivatives of sapogenin were synthesized with different substituent groups in the C 28 position, and their yields are listed in Table 1.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Purified sapogenin is an amorphous powder with a purity of 91.62% by HP 1100 HPLC (Agilent, Santa Clara, CA, U.S.A.) in the following operating conditions: column, Hypersil ODS (250 × 4.6 mm, 5 μm); flow phase, methanol/water (80:20); injection volume, 10 μL; flow rate, 1 mL/min; temperature, 25 °C; and wavelength, 218 nm. IR spectra and 1 H and 13 C NMR data showed that it had a sapogenin structure with formula C 30 H 48 O 5 , which is consistent with our former literature. 9 A total of 19 derivatives of sapogenin were synthesized with different substituent groups in the C 28 position, and their yields are listed in Table 1.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…9 A total of 19 derivatives of sapogenin were synthesized with different substituent groups in the C 28 position, and their yields are listed in Table 1. All products were measured by IR, mass spectrometry (MS), and 1 H and 13 C NMR to confirm their structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 16 was successfully converted to 17 by the reaction with S,S -diphenylphosphorodithioate (PSS) [ 20 ] in the presence of triisopropylbenzenesulfonyl chloride (TPSCl) and tetrazole in pyridine, in a yield of 79%. Considering the instability of phenylthio group under basic conditions [ 21 ], acetyl chloride in methanol (AcCl/MeOH) [ 22 ] was applied to the deacetylation of 17 . When 1.2 equivalent of AcCl was utilized, compound 17 was successfully converted to 18 .…”
Section: Resultsmentioning
confidence: 99%